2007
DOI: 10.1016/j.yhbeh.2007.03.016
|View full text |Cite
|
Sign up to set email alerts
|

The ram as a model for behavioral neuroendocrinology

Abstract: The sheep offers a unique model to study male sexual behavior and sexual partner preference. Rams are seasonal breeders and show the greatest libido during short days coincident with the resumption of ovarian cyclicity in the ewe. Threshold concentrations of testosterone are required for the acquisition and display of adult sexual behavior. In addition, estrogens produced from circulating testosterone by cytochrome P450 aromatase in the preoptic area are critical for the maintenance of sexual behaviors in rams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 62 publications
(68 reference statements)
3
44
1
4
Order By: Relevance
“…Although Perkins and Roselli (2007) reported that some sexually inactive rams would begin to copulate if provided with additional opportunities, the results of the present study demonstrated that sexual performance tests did not improve the sexual activity of young bucks (P = 0.427) (data are not given). This finding is in line with the finding that bucks do not require sexual experience with estrus females to reach complete serving capacity (Price et al, 1998).…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Although Perkins and Roselli (2007) reported that some sexually inactive rams would begin to copulate if provided with additional opportunities, the results of the present study demonstrated that sexual performance tests did not improve the sexual activity of young bucks (P = 0.427) (data are not given). This finding is in line with the finding that bucks do not require sexual experience with estrus females to reach complete serving capacity (Price et al, 1998).…”
Section: Discussioncontrasting
confidence: 88%
“…Serving capacity and sexual performance tests can be used to predict pasture-mating efficiency in rams (Perkins and Roselli, 2007). However, these types of test are not common practices for small ruminants and there is less interest and fewer studies associated with sexual performance in goats compared with other livestock species (Flores et al, 2000;Darwish and Mahboub, 2011;Moghaddam et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…$ These two authors contributed equally. Roselli, 2007;Pfaus and Heeb, 1997;Kollack-Walker and Newman, 1995;Heeb and Yahr, 1996;Wade and Arnold, 2004), and we limit our discussion to the hormonal control of mating and aggression in male mice. Testosterone is required in a reversible manner in adult rodents for the display of male typical behaviors.…”
mentioning
confidence: 99%